G171 Improving situation awareness in prescribing: A medication safety huddle – the DRUG-gle (Druggle). (27th April 2016) - Reece, A; Hill, A; Platt, B; Burridge, R
Abstract : Aims: Aims of this quality improvement intervention: Alert doctors and nurses on the paediatric ward to common prescribing errors Change behaviour improving prescribing and reducing errors Understand the pharmacists' "interventions" written in green pen on the medication chart Lead to a reduction in pharmacist "interventions" and safer prescribing Methods: Using the safety 'huddle' as a blue-print, a short, focussed discussion between the ward doctors, nurses and pharmacist was devised, called a DRUG-gle (Druggle). One simple question was asked of the pharmacist: "What "interventions" have you made on the charts today?". Going through every "intervention", in effect every green pen correction on the prescription charts, took too much time, so a focussed discussion of the top 3, or most important intervention/s was facilitated by the pharmacist. These were captured in order to share the learning points with the wider team. Results: The DRUG-gle happens ad hoc with the lead consultant and the ward pharmacist, with an aim to start organically and vuild up to embed it into the routine of the ward. The interventions were translated into accessible, bite-sized, relevant learning points, formatted into a one-page 'DRUG-gle' sheet, sent to the team by e-mail. The markers of success (and measurements) would be: Reduction in reported drug errors (DATIX reports) Reduction in pharmacist "interventions" (monthly audit) Confidence in team's prescribing skills (self assessment questionnaire). Challenges identified include relying on a senior doctor and the pharmacist to drive it, having time to do it on a full and busy ward, embedding it into other safety initiatives on the ward and in our department and the frequent change in junior staff making demonstrable impact during their brief time in our speciality challenging. Conclusion: Similarly to the safety huddle, the measurement of the DRUG-gle's true value may lie in the behaviours around situation awareness, and in multi-disciplinary working, to creating a positive safety culture around the prescribing and administration of medications on the paediatric ward.